Estimating the Cost and Utility of Statewide Travel Models using Scenario-Based Interviews. Issue 1 (January 2019) - Francis, Daniel; Tsang, Flavia; Erhardt, Gregory D.
Statewide travel models are analysis tools that simulate transportation system conditions and are used to answer "what if" questions about proposed plans and policies. In the United States, they are in use or in development in 39 out of 50 state departments of transportation (DOTs). States without a statewide model are faced with the decision of whether to invest in one, whereas states with models need to decide when and whether to upgrade. Prior efforts to aid this decision making provided detailed synthesis on the cost of statewide modeling, but it has been difficult for other states to use the lessons learned, because cost is largely driven by each state's specific circumstances. There has also been very little research on quantifying the value of models. To address these gaps, the present research uses a novel scenario-based interview approach. Representatives from 29 DOTs and five consultancies participated in our scenario-based interviews, from which we collected cost estimates for three archetypical statewide models and willingness-to-pay estimates (i.e., perceived value) under nine model development and policy focus scenarios. Our results show that cost ranges from 500, 000 for an archetypical Basic 3-Step Model to between 2.8 million and 5 million for an Activity-Based Model for a large state, with data collection comprising a large portion of the cost (36–66%). Further, the perceived value of statewide models exceeds the costs by a factor of 2.4–11.3, with the cost–benefit ratio being higher when a DOT is interested in a broader set of policy issues.